2019
DOI: 10.1080/23279095.2019.1660881
|View full text |Cite
|
Sign up to set email alerts
|

The Executive Checklist (EC-10) – a new rating instrument for clinicians assessing dysexecutive behavior

Abstract: Assessment of executive functions (EF) is often criticized for its lack of ecological validity. As a consequence, several self-and partner rating scales for EF have been developed, while rating scales designed for clinicians are lacking. We therefore developed the Executive Checklist (EC-10), a new rating scale for clinicians assessing dysexecutive behavior during neuropsychological assessment and examined its psychometric properties. Consecutive referrals from a memory clinic with subjective cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For example, Biederman et al found only modest overlap between neuropsychological tests of EF and behavioral ratings, with neuropsychological tests proving more effective in identifying lower IQ, and behavioral ratings proving more effective in identifying higher levels of core ADHD symptoms (Biederman et al, 2008). Other studies on this topic have replicated Biederman and colleagues concerns about this modest association and have shown the limited ecological validity of neuropsychological tests (Burgess et al, 1998;Soto et al, 2020;Viklund et al, 2021). Further, different neuropsychological tests of EF may assess various cognitive factors underpinning EF, such as inhibition, cognitive flexibility, and working memory (Burgess et al, 1998), suggesting that any one neuropsychological test may not capture the full scope of the clinical impairment associated with EF deficits.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Biederman et al found only modest overlap between neuropsychological tests of EF and behavioral ratings, with neuropsychological tests proving more effective in identifying lower IQ, and behavioral ratings proving more effective in identifying higher levels of core ADHD symptoms (Biederman et al, 2008). Other studies on this topic have replicated Biederman and colleagues concerns about this modest association and have shown the limited ecological validity of neuropsychological tests (Burgess et al, 1998;Soto et al, 2020;Viklund et al, 2021). Further, different neuropsychological tests of EF may assess various cognitive factors underpinning EF, such as inhibition, cognitive flexibility, and working memory (Burgess et al, 1998), suggesting that any one neuropsychological test may not capture the full scope of the clinical impairment associated with EF deficits.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the recent emphasis on the use of functional measures in the evaluation process (Barkley, 2014;Garcia-Barrera et al, 2014;Holst & Thorell, 2018;Isquith et al, 2013;Thorell & Catale, 2014;Toplak et al, 2013;Viklund et al, 2019) and the still limited availability of functional measurement instruments (Naglieri & Goldstein, 2014), especially in the Brazilian context (e.g. SATEPSI search, updated in April/2020, not resulting in the location of instruments), the future availability of IFERA-II may constitute an important contribution.…”
Section: Closing Of Ifera-ii Final Versionmentioning
confidence: 99%
“…By developing and presenting a new functional measure, the present study aimed to contribute to the discussion on the ecological validity of EFs measures (Garcia-Barrera et al, 2014;Isquith et al, 2013;Roth et al, 2014;Viklund et al, 2019;Zimmermann et al, 2014) and to minimize the current limitations regarding the availability of these measures, which creates some obstacles for the multi-method evaluation of EFs, as suggested by several authors (Garcia-Barrera et al, 2014;Isquith et al, 2013). From this study, the final version of IFERA-II was created, and new investigations are underway to verify its psychometric properties, including information about its reliability and evidence of validity (convergence with other variables and external criteria).…”
Section: Closing Of Ifera-ii Final Versionmentioning
confidence: 99%
See 2 more Smart Citations